The role of renewable energy technological innovation on climate change: Empirical evidence from China - Lin, Boqiang; Zhu, Junpeng (The Science of the total environment, 2019)
To develop renewable energy as well as promote China's transition to a low-carbon economy, the government needs to pay attention to renewable energy technological innovation (RETI). Using China's provincial panel data from 2000 to 2015, and regarding the CO2 emissions as the proxy of climate change, this paper identifies the relationship between RETI and CO2 emissions as well as seeks to confirm the role of RETI on climate change. The linear regression model confirms that the RETI has a significant negative effect on CO2 emissions. In addition, considering the disparities of energy structure, the impacts of RETI on CO2 emissions may be distinct. We, therefore, construct a panel threshold model by taking into account the distinct effect of RETI under different energy structure. We find that the effect of RETI on curbing CO2 emissions decreases with the rising of coal-dominated energy consumption structure but in contrast, this effect increases with the growing proportion of renewable energy generation. This paper provides new insight into the relationship between technological innovation and climate change. Based on these findings, some relevant policy recommendations are proposed. [Display omitted] •We identify the relationship between renewable energy technological innovation (RETI) and CO2 emissions.•We find distinct effect of RETI on curbing CO2 under different energy structure.•The government should pay attention to the role of RETI.•More renewable energy should be encouraged in residential life and production process.